Pharmacy-Based Point-of-Care Testing: How a “Standard of Care” Approach Can Facilitate Sustainability - Alex J. Adams (University of Minnesota Libraries Publishing, 2021)
COVID-19 spurred rapid expansion of pharmacy-based point-of-care testing (POCT). This growth was aided, in part, by federal guidance that removed state-level regulatory uncertainty surrounding the ability of pharmacists to administer, interpret, and act on the results of tests. Surveys suggest there is considerable confusion about the legality of these services by state regulators. To ensure the sustainability of POCT services over time, states should consider adopting a standard of care approach to regulation, allowing a flexible framework for practice innovation and expansion over time.